The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fphys.2019.00499
|View full text |Cite
|
Sign up to set email alerts
|

Crohn’s Disease in Clinical Remission Is Marked by Systemic Oxidative Stress

Abstract: Introduction: Crohn’s disease (CD) is characterized by chronic and relapsing inflammation of the gastro-intestinal tract. It is assumed that oxidative stress contributes to CD pathogenesis, but systemic biomarkers for oxidative stress in CD are not yet identified. A reduction in free thiol groups in plasma proteins (“plasma free thiols”) reflects systemic oxidative stress since they are prime substrates for reactive oxygen species. Here, we determined the concentrations of plasma free thiols in CD p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 57 publications
3
50
0
Order By: Relevance
“…Mean serum free thiol concentrations were 780 ± 80.9 µM for reproductive women and 762.9 ± 85.3 µM for menopausal women (p < 0.001 after correction for age, Figure S1). Concentration ranges of serum free thiols were in accordance with previous studies that used the same detection method [20][21][22][23][24]. Median age of reproductive women was 30 years (interquartile range (IQR) 22-42 years), whereas menopausal women had a median age of 54 years (IQR: 50-59 years).…”
Section: Cohort Characteristicssupporting
confidence: 84%
“…Mean serum free thiol concentrations were 780 ± 80.9 µM for reproductive women and 762.9 ± 85.3 µM for menopausal women (p < 0.001 after correction for age, Figure S1). Concentration ranges of serum free thiols were in accordance with previous studies that used the same detection method [20][21][22][23][24]. Median age of reproductive women was 30 years (interquartile range (IQR) 22-42 years), whereas menopausal women had a median age of 54 years (IQR: 50-59 years).…”
Section: Cohort Characteristicssupporting
confidence: 84%
“…CD is characterized by chronic transmural and segmental intestinal inflammation that can affect any part of the gastrointestinal tract. The etiopathogenesis is complex and multifactorial, and is not totally clear yet [ 30 ]. Patients typically experience periods of flare-ups and symptomatic remission, which are difficult to predict and treat adequately [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have found it to drop only in active disease, either because patients in remission had its concentrations at the levels observed in healthy individuals [24] or because only patients in active phase had been enrolled [25,55]. Low albumin concentration is one of the predictors of malnutrition [54] and its decrease in IBD patients, particularly in the active phase of the disease, is likely to reflect the disease-associated worsening of nutritional status. The similar function of an indicator of nutritional status can be fulfilled by transferrin, which also decreases solely in IBD patients with active disease [56] (Table 1).…”
Section: Diagnostic Markers In Ibd (Markers Not Specific For Either Umentioning
confidence: 99%
“…Bourgonje et al [54] evaluated albumin-adjusted thiols exclusively in CD patients in remission and observed that their depletion is related to the disease extent, as the index was significantly lower in patients with ileocolonic involvement than colonic. Additionally, it was inversely related with the severity of inflammation.…”
Section: Progression Markers In CDmentioning
confidence: 99%